Pelatihan Penelitian Tindakan Kelas Kepada Guru SDN 001 Rimba Sekampung Dumai - Hanifatul Rahmi; Adelia Alfama Zamista; Juni Saputra (Politeknik Negeri Cilacap, 2019)
The purpose of implementing Community Service is to provide knowledge to teachers which includes: Strategy for writing classroom action research. The material for writing classroom action research strategies begins with introducing the activities that must be carried out by the teacher before classroom action research, explaining to the teacher to find problems that can be raised as research material, solutions that can be used as alternative learning improvements, classroom action research concepts, research designs class action, compiling a proposal for classroom action research proposal, assessing classroom action research reports, student value data is valuable data that can be analyzed and described as main data and describes how to search references from various sources. Participants also received guidance on writing classroom action research on classroom action research tutorials and practice activities. The trainees were 15 teachers from SDN 001 Rimba Sekampung. After training, the results obtained are: Increased teacher's ability to seek effective learning, Understanding Classroom Action Research Concepts, Understanding Classroom Action Research Design Arrangements, Compiling Classroom Action Research Proposals, Can provide assessment of Classroom Action Research reports.